(untitled) (Contemporary Mathematics, 2025)
In this article, we present an averaging limit theorem for impulsive delay Caputo fractional stochastic differential equations. In contrast to the present literature, a new technique is adopted to overcome the difficulties hired by the impulsive term based on impulsive-type Grönwall inequality. As a result, it is proved that the solution of the non-impulsive averaged delay Caputo fractional stochastic differential equations converges to that of the standard impulsive delay Caputo fractional stochastic differential equations in Lq-sense. Finally, an example is constructed to enhance the analytical result.